2010
DOI: 10.1111/j.1349-7006.2010.01816.x
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐96 and miR‐183 detection in urine serve as potential tumor markers of urothelial carcinoma: correlation with stage and grade, and comparison with urinary cytology

Abstract: A new diagnostic marker for urothelial carcinoma (UC) is needed to avoid painful cystoscopy during the initial diagnosis and follow-up period. However, the current urine markers are useless because of the low sensitivities and specificities for UC detection. MiR-96 and miR-183 were differentially upregulated microRNA in our previous microRNA screening for UC. The expression levels of miR-96 and miR-183 in the urine samples were significantly higher in 100 UC than in healthy controls (miR-96, P = 0.0059; and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 36 publications
8
144
3
1
Order By: Relevance
“…They further found that expression of these miR along with miR-149, -181b, -205, and -375 correctly identified PC from normal tissue with an area under the curve of 0.88 (34). miR-96 and miR-182 are expressed at a high level in urothelial carcinoma and detection of the miR in urine correlated with disease stage and grade (35). Dai et al (36) recently reported a 10-fold increase in miR-183-96-182 cluster expression in splenocytes in a mouse model of lupus, suggesting a role for this cluster in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…They further found that expression of these miR along with miR-149, -181b, -205, and -375 correctly identified PC from normal tissue with an area under the curve of 0.88 (34). miR-96 and miR-182 are expressed at a high level in urothelial carcinoma and detection of the miR in urine correlated with disease stage and grade (35). Dai et al (36) recently reported a 10-fold increase in miR-183-96-182 cluster expression in splenocytes in a mouse model of lupus, suggesting a role for this cluster in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the expression of miR-183-5p in 104 urothelial carcinomas (4.225±0.414) was significantly higher than that in 31 normal bladder epitheliums (1.224±0.224, P<0.0001) (Fig. 3B) (27). All of the eligible expression data of miR-183-5p extracted from TCGA, one GEO microarray and one literature research provided an overall SMD of 3.76 (0.34-7.19) as analyzed by STATA software (Fig.…”
Section: Mir-183-5p Expression Level From Geo and Literaturesmentioning
confidence: 99%
“…miR-183-5p, located on chromosome 7q32.2, has been studied in various types of cancers, such as human breast cancer (20), esophageal squamous cell carcinoma (21), esophageal squamous cell carcinoma (22), gastric cancer (23), human pancreatic adenocarcinoma (24) and melanoma (25). The expression of miR-183 in BC patients was higher in tissues (26)(27)(28) and serum (29) and showed a moderate value of the BC diagnosis (27). However, no functional study of miR-183-5p in BC has been reported previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mihelich et al (26) identified the members of this cluster as having diagnostic and prognostic implications in prostate cancer. In addition, Yamada et al (27) identified two members of the cluster, miR-96 and miR-183 serve as potential tumor markers of urothelial carcinoma and Weeraratne et al (28) reported that the effects of the miR-183/96/182 cluster converge to regulate cell survival, proliferation and migration in medulloblastoma. The miR-183/96/182 cluster was also found to regulate oxidative apoptosis and sensitize cells to chemotherapy in gliomas (16,(25)(26)(27)(28)(29).…”
Section: Simultaneous Knockdown Of the Expression Of The Mir-183/96/1mentioning
confidence: 99%